Histological Findings in Unclassified Sudden Infant Death, Including Sudden Infant Death Syndrome. (May 2013) - Liebrechts-Akkerman, Germaine; Bovee, Judith V.M.G.; Wijnaendts, Liliane C.D.; Maes, Ann; Nikkels, Peter G.J.; de Krijger, Ronald R.
Our objective was to study histological variations and abnormalities in unclassified sudden infant death (USID), including sudden infant death syndrome (SIDS), in The Netherlands. Two hundred Dutch USID cases between 1984 and 2005 were identified. The histology slides and autopsy reports of 187 cases were available for systematic review, including brain autopsy in 135 cases. An explanation for the cause of death in 19 patients (10.2%) was found. Twelve patients had bronchopneumonia, 3 showed extensive aspiration, 2 had signs of a metabolic disorder, 1 had sepsis, and 1 had meningitis. Frequent nonspecific findings were congestion (66%), edema (47%), small hemorrhages (18%), and lymphoid aggregates (51%) in the lungs; congestion of the liver (23%); and asphyctic bleeding in the kidney (44%), adrenal gland (23%), and thymus (17%). Statistical associations were found for infection with starry sky macrophages in the thymus ( P = 0.004), with calcification ( P = 0.023), or with debris in the Hassal's corpuscles ( P = 0.034). In this study, in 10.2% of cases the histological findings were incompatible with SIDS or USID. Furthermore, several frequent nonspecific histological findings in the thymus that point toward an infection were found.